Implementasi Metode K-Nearest Neighbors Pada Sistem Klasifikasi Kualitas Udara Berdasarkan Partikulat Berbahaya Yang Terkandung - Sudarmawan, I Komang Roni; Kadyanan, I Gusti Agung Gede Arya; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Air pollution is one of the most dangerous issues for health in the current industrial 4.0 era. Air quality, especially in big cities such as Jakarta, which is the capital of Indonesia as well as the center of government, is an issue that is being eradicated by the government. With a very high percentage of the productive age of the population in the city of Jakarta, motor vehicle activity in the city of Jakarta will also be equivalent to the productive age of the population of the city of Jakarta. This study will design an air quality classification system using the K-Nearest Neighbors method. Before being classified, a data preprocessing process will be carried out, such as handling missing values ??and handling outliers. In addition, because the data obtained is quite small, a K-Fold Validation process will be carried out for the model selection process. Finally, the performance evaluation of the model will be carried out using the confusion matrix method .